Apakah Risiko Bisnis, Kepemilikan Manajerial dan Intellectual Capital Memiliki Pengaruh Terhadap Nilai Perusahaan? - Majidah; Ary Noor Setyaningsih (Jurnal Akademi Akuntansi, 2024)
Purpose: This study intends to investigate the simultaneous and partial effects of business risk, managerial ownership, and intellectual capital on firm value in the energy sector listed on the Indonesia Stock Exchange during the 2017–2021 period. Methodology/approach: This study used quantitative data with sampling criteria and obtained 130 observations from 26 companies. Panel data regression with Eviews 12 was used to analyze the observatory data. Findings: The research results show that only managerial ownership has a positive effect on firm value. Practical and Theoretical contribution/Originality: Managerial ownership is one of the factors investors consider when making investment decisions. Managerial ownership can minimize agency problems. The energy sector on the IDX tends to depend on natural resources, so intellectual capital is only supported by value-added human capital. Research Limitation: The adjusted R2 is only 14.28%. Only managerial ownership is a determinant of firm value.